Conservación del patrimonio cultural inmaterial e Identidad cultural en el cantón Guano, Provincia de Chimborazo. - Zavala Morales, Joaho Patricio (2025)
The current study Conservation of Intangible Cultural Heritage and Cultural Identity in Guano Canton, Chimborazo Province investigates the interplay between the preservation of intangible cultural heritage and the cultural identity of Guano Canton. This region, rich in intangible cultural assets, has seen these traditions threatened by various factors, including acculturation, technological advancements, and globalization. This qualitative research uses descriptive, correlational, cross-sectional, and non-experimental methodologies, incorporating both fieldwork and documentary analysis. The study engaged key stakeholders, including the Tourism Director and local residents who constituted the sample population. Surveys utilizing a Likert scale were administered to assess the value placed on the intangible cultural heritage and its connection to cultural identity. Statistical analysis using Spearman’s Rho in SPSS revealed no significant correlation between the variables of intangible cultural heritage and cultural identity. Nonetheless, the findings indicate that participants highly value their ancestral knowledge, expressing a strong desire to preserve these traditions. Despite ongoing challenges, there is considerable local interest in safeguarding cultural heritage as a means of preserving the unique cultural identity of the region.